Individualized care for older adults with diabetes and its relationship with communication, psychosocial self‐efficacy, resources and support for self‐management and socio‐demographics - Birute Bartkeviciute; Olga Riklikiene; Rima Kregzdyte; Vita Lesauskaite (Wiley, 2023)
Abstract Aim To examine the relationship between patient-provider communication, psychosocial patient self‐efficacy, resources and support for self‐management and socio‐demographics within individualized care of older adults with diabetes. Design A quantitative study with a cross‐sectional survey design. Methods Data were collected from September 2019 to January 2021 using: Individualized Care Scale, The Communication Assessment Tool, The Diabetes Empowerment Scale and The Resources and Support for Self‐Management Scale. Patients with either Type 1 or Type 2 diabetes mellitus that were 65 years old and over (N = 145) participated in the study. Results The most positive aspects of patient-provider communication were respect and creating a comfortable environment for the patient. A significant relationship was observed between patients' perceptions and support of individualized care and diabetes‐related measures. Effective communication was the main factor associated with support for individualizing care, and together with education level, empowerment and access to resources, explained 23% of the variance.